The Role of Human Capital in Non- oil Exports in the Kingdom of Saudi Arabia from 1981 to 2014 - Al- sufyani, Norah Obaidallah (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed at assessing the long- term relationship between human capital development and non- oil exports in the Kingdom from 1981 to 2014. The study assumes that there is a direct relationship between the increase in non- oil exports of the Kingdom and the interest in human capital and global income, and an inverse relationship between the increase in non- oil exports of the inflation rate. To achieve this goal, an autoregressive model of distributed lag (ARDL) has been used. The study has found a long- term relationship between the variables, and what explains this relationship is the global income, which is directly related to non- oil exports, and inflation, which has an inverse relationship with non- oil exports, according to the hypotheses of the study on global income and inflation. As for spending on developing human capital and health and social development, it has appeared to be insignificant and does not affect non- oil exports, and this contradicts the hypotheses of the study for this part due to the mismatch of the graduates' majors with the labor market requirements, and the overcrowding of foreign labor against national labor. The study has recommended conducting extensive studies to determine the needs of the labor market in different fields, encouraging young people to establish private projects and supporting them by offering loans and providing facilities, and increasing Saudization in private sectors instead of foreign labor in addition to the optimal allocation of financial resources, such as spending on human resources development and on health and social development.
Keywords: diversifying the economic base; human resource development; health and social development; training and development; spending on education; spending on health